Dora's Toy Stories - Videau, Valerie; Nickelodeon (Television network); Nick Jr. (Firm) (New York : Simon Spotlight/Nickelodeon., 2011)
Dora meets Jack, a funny jack-in-the-box, at a toy store, while Boots has lost his stuffed dinosaur and must find it in order to sleep.
aAt head of titlle: Nickelodeon Dora the explorer.
a"Based on the screenplays "Dora's Jack-in-the-Box" written by Rosemary Contreras and "Boots Cuddly Dinosaur" written by Chris Gifford.
a"Based on the TV series Dora the Explorer as seen on Nick Jr."--T.p. verso.
aInclude a bookmark.
Text mainly in English with some Spanish words.
Keywords: Dora the Explorer (Fictitious character) -- Juvenile fiction; Explorers -- Juvenile fiction; Girls -- Juvenile fiction; Adventure fiction